Answer:
<em>x\</em><em>y</em><em>=</em><em>5</em><em>\</em><em>3</em><em>.</em><em> </em><em> </em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>[</em><em>I]</em>
<em>X=</em><em>5</em><em>y</em><em>\</em><em>3</em>
<em>X+</em><em>y</em><em>=</em><em>5</em><em>6</em>
<em>X=</em><em>5</em><em>6</em><em>-</em><em>y</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>[</em><em>ii</em><em>]</em>
<em>substitute</em><em> [</em><em>I]</em><em> </em><em>&</em><em>[</em><em>ii]</em>
<em>5</em><em>y</em><em>\</em><em>3</em><em>=</em><em>5</em><em>6</em><em>-</em><em>y</em>
<em>5</em><em>y</em><em>=</em><em>3</em><em>[</em><em>5</em><em>6</em><em>-</em><em>y</em><em>]</em>
<em>5</em><em>y</em><em>=</em><em>1</em><em>6</em><em>8</em><em>-</em><em>3</em><em>y</em>
<em>5</em><em>y</em><em>-</em><em>3</em><em>y</em><em>=</em><em>1</em><em>6</em><em>8</em>
<em>2</em><em>y</em><em>=</em><em>1</em><em>6</em><em>8</em>
<em>y=</em><em>1</em><em>6</em><em>8</em><em>\</em><em>2</em>
<em>y=</em><em>8</em><em>4</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em><em>[</em><em>iii</em><em>]</em>
<em>substitute</em><em> </em><em>[</em><em>iii</em><em>]</em><em> </em><em>in </em><em>[</em><em>ii]</em>
<em>X=</em><em>5</em><em>6</em><em>-</em><em>8</em><em>4</em>
<em>X=</em><em>-</em><em>2</em><em>8</em>
<em>x-y=</em><em>-</em><em>2</em><em>8</em><em>-</em><em>8</em><em>4</em>
<em>=</em><em>-</em><em>1</em><em>1</em><em>2</em>